2020
DOI: 10.3390/v12060624
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chemical Protocols for Inactivating SARS-CoV-2 Infectious Samples

Abstract: Clinical samples collected in coronavirus disease 19 (COVID-19), patients are commonly manipulated in biosafety level 2 laboratories for molecular diagnostic purposes. Here, we tested French norm NF-EN-14476+A2 derived from European standard EN-14885 to assess the risk of manipulating infectious viruses prior to RNA extraction. SARS-CoV-2 cell-culture supernatant and nasopharyngeal samples (virus-spiked samples and clinical samples collected in COVID-19 patients) were used to measure the reduction of infectivi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
94
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 17 publications
9
94
3
1
Order By: Relevance
“…Given no virus was detected in serial passage of the treated samples it is probable that treatment with either of these buffers is effective at inactivating SARS-CoV-2. A previous study reported that Buffer AVL either alone or in combination with ethanol was not effective at completely inactivating SARS-CoV-2(17). By contrast, we could not recover any infectious virus from samples treated with AVL plus ethanol, consistent with previous studies indicating that AVL and ethanol in combination is effective at inactivating of a wide range of different viruses and other pathogens, and the results presented may be used to directly inform and improve the design of future inactivation studies.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Given no virus was detected in serial passage of the treated samples it is probable that treatment with either of these buffers is effective at inactivating SARS-CoV-2. A previous study reported that Buffer AVL either alone or in combination with ethanol was not effective at completely inactivating SARS-CoV-2(17). By contrast, we could not recover any infectious virus from samples treated with AVL plus ethanol, consistent with previous studies indicating that AVL and ethanol in combination is effective at inactivating of a wide range of different viruses and other pathogens, and the results presented may be used to directly inform and improve the design of future inactivation studies.…”
supporting
confidence: 89%
“…Furthermore, the precise composition of many commercial reagents is proprietary, preventing ingredient-based inference of inactivation efficacy between reagents. Some limited preliminary data on SARS-CoV-2 inactivation by heat (14,15) or chemical (16)(17)(18)(19)(20)(21) Vero E6 cells at a multiplicity of infection (MOI) of 0.001, in the presence of 5% FCS. Cell culture supernatants were collected 72 hours post infection, clarified for 10 mins at 3000 × g, aliquoted and stored at -80°C until required.…”
Section: Introductionmentioning
confidence: 99%
“…However, 56 • C-30 min appears much less efficient on SARS-CoV-2 than on transmissible swine gastroenteritis virus, an alpha coronavirus, showing a reduction in infectivity of >7.5 Log 10 units [12]. This suggests that the inactivation of clinical samples ahead of molecular diagnosis should also consider chemical inactivation as an alternative to heat inactivation for SARS-CoV-2 diagnostics [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the precise composition of many commercial reagents is proprietary, preventing ingredient-based inference of inactivation efficacy between reagents. Some limited preliminary data on SARS-CoV-2 inactivation are available (14)(15)(16)(17)(18)(19), but given the current level of diagnostic and research activities, there is an urgent need to comprehensively investigate SARS-CoV-2-specific inactivation efficacy of available methods to support safe virus handling.…”
Section: Introductionmentioning
confidence: 99%
“…However, our observation that residual virus could be recovered from most treated samples indicates that these media cannot be assumed to completely inactivate SARS-CoV-2 in samples and that additional precautionary measures should be taken in laboratories when it comes to sample handling and transport.Limited SARS-CoV-2 inactivation data on molecular extraction reagents used in nucleic acid detection assays are currently available. One study reported that Buffer AVL either alone or in combination with ethanol was not effective at completely inactivating SARS-CoV-2(15).By contrast, we could not recover any infectious virus from samples treated with AVL plus ethanol, consistent with previous studies indicating that AVL and ethanol in combination is effective at inactivating MERS and other enveloped viruses (10, 34), and indicating that both AVL and ethanol steps of manual extraction procedures should be performed before removal of samples from primary containment for additional assurance. Our detergent inactivation data, indicating that SDS, Triton X-100 and NP40, but not Tween 20, can effectively inactivate SARS-CoV-2 in tissue culture fluid and in pooled NP and OP swab fluid, corroborate findings of a recent study (17); however, as has been demonstrated for other viruses (31), we observed an inhibitory effect of serum on virus inactivation by detergent, highlighting the importance of validating inactivation methods with different sample types.…”
mentioning
confidence: 99%